2007
DOI: 10.1007/s00125-007-0633-0
|View full text |Cite
|
Sign up to set email alerts
|

Addition of vildagliptin to insulin improves glycaemic control in type 2 diabetes

Abstract: Aims/hypothesis Type 2 diabetes is difficult to manage in patients with a long history of disease requiring insulin therapy. Moreover, addition of most currently available oral antidiabetic agents increases the risk of hypoglycaemia. Vildagliptin is a dipeptidyl peptidase-IV inhibitor, which improves glycaemic control by increasing pancreatic beta cell responsiveness to glucose and suppressing inappropriate glucagon secretion. This study assessed the efficacy and tolerability of vildagliptin added to insulin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
310
4
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(351 citation statements)
references
References 16 publications
25
310
4
12
Order By: Relevance
“…These favourable results were obtained with no weight gains or increases in the incidence of hypoglycaemia. A reduction in severe hypoglycaemic episodes was reported in one trial of insulin plus vildagliptin in T2DM patients poorly controlled with high doses of insulin, presumably because of an individual reduction in daily insulin dosage (which resulted in a smaller HbA 1c reduction of only 0.3%) [66]. In the TRANSITION randomized controlled trial [70], significantly greater reductions in HbA 1c (-1.44% vs -0.89%; P<0.001) and plasma glucose levels were achieved with the combination of insulin detemir + sitagliptin + metformin compared with sitagliptin + metformin ± SU, with no increases in the rate of hypoglycaemia.…”
Section: Gliptins Combined With Insulin In Type 2 Diabetes Mellitusmentioning
confidence: 93%
See 1 more Smart Citation
“…These favourable results were obtained with no weight gains or increases in the incidence of hypoglycaemia. A reduction in severe hypoglycaemic episodes was reported in one trial of insulin plus vildagliptin in T2DM patients poorly controlled with high doses of insulin, presumably because of an individual reduction in daily insulin dosage (which resulted in a smaller HbA 1c reduction of only 0.3%) [66]. In the TRANSITION randomized controlled trial [70], significantly greater reductions in HbA 1c (-1.44% vs -0.89%; P<0.001) and plasma glucose levels were achieved with the combination of insulin detemir + sitagliptin + metformin compared with sitagliptin + metformin ± SU, with no increases in the rate of hypoglycaemia.…”
Section: Gliptins Combined With Insulin In Type 2 Diabetes Mellitusmentioning
confidence: 93%
“…Therefore, it may also be possible to speculate on the clinical efficacy of combining a DPP-4 inhibitor with insulin. Four placebo-controlled trials have investigated the clinical efficacy and safety of adding a DPP-4 inhibitor to a basal insulin regimen (with or without metformin or SU; Table 4) [66][67][68][69]. All studies reported consistent results, with a reduction in HbA 1c levels of 0.5-0.6% on average if daily insulin dosages were maintained unchanged.…”
Section: Gliptins Combined With Insulin In Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…DPP-4 inhibitors can also be added to insulin, which reduces HbA 1c , minimizes the risk for hypoglycaemia [30].…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
“…Vildagliptin added to TZD was associated with a 5.6% decrease in total cholesterol vs. TZD alone and a 10.5% decrease in LDL-C vs. TZD alone (56). Added to insulin, vildagliptin decreased total cholesterol and LDL-C, 4.0% and 5.8% vs. insulin alone, respectively (57). The largest improvements relative to control were observed in an active comparator trial with rosiglitazone.…”
Section: Sitagliptinmentioning
confidence: 93%
“…It is available in Brazil and Mexico as both a 50mg and 100mg daily dose and at the publication of this review, had been approved for use in the European Union (EU), recommended as a 50mg once-daily dose with a sulfonylurea or as 50 mg twice-daily in combination with either metformin or a TZD. Vildagliptin has been studied as a monotherapy (66)(67)(68)(69) in combination with other oral antidiabetic agents (55)(56)(57)70,71), and against active comparator therapies including TZDs (72) and metformin (58). The maximum daily dose used in clinical trials of vildagliptin was 100mg (oncedaily or 50mg twice-daily); other lower doses regimens were also investigated.…”
Section: Sitagliptinmentioning
confidence: 99%